(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This paper will examine the depiction of conflict within Getting Out (1977) and ‘night, Mother (1982) written by Marsha Norman using the ideas of Max Weber. In spite of the fact that much of the existing literature on these plays focuses on the feminist and psychoanalytic approaches, this research proposes a sociological analysis of the works and will show how the conflict becomes entrenched within the structure of social relations. The study is based on a qualitative interpretative method that relies on textual analysis. Certain scenes of the plays will be chosen to reveal the nature of the conflict and its social causes. These will be defined according to the basic categories of Weber’s sociology, such as class, status, power, domination, and legitimation. It is clear that conflicts in both plays emerge on different levels including interpersonal, family, and societal and have much to do with structural inequality. While Getting Out focuses on conflict as an outside phenomenon when the protagonist tries to gain autonomy and be reintegrated into society amidst resistance, ‘night, Mother features a conflict on an internal level, resulting in self-destruction because of the lack of agency and social repression. As shown from the findings, conflict is an inseparable part of social life but can result in either success or tragedy based on whether people can resist and have adequate resources. As can be seen, the study makes a valuable contribution to literature studies through introducing a Weberian theoretical analysis of Norman’s plays which creates a connection between sociology and literary studies.